The Final, Anticlimactic Rude on Baby Doe - Murray, Thomas H. (The Hastings Center report, 1985)
DHHS's rule on the care of imperiled newborns has a symbolic significance for the groups that struggled for compromise, but it will have a minimal impact on medical and moral decision making.